Training-related and competition-related risk factors for respiratory tract and gastrointestinal infections in elite cross-country skiers - Svendsen, I. S.; Taylor, I. M.; Tonnessen, E.; Bahr, R.; Gleeson, M. (British Journal of Sports Medicine, 2016)
Aim To examine symptoms indicative of respiratory tract and gastrointestinal infections and determine risk factors for such symptoms in elite cross-country skiers.